Dermoscopy of a single plaque on the face: an uncommon presentation of cutaneous sarcoidosis - Claudio Conforti (Mattioli1885, 2018)
Sarcoidosis is a multisystemic granulomatous disease of unknown causes, and cutaneous sarcoidosis (CS) is an early manifestation of the disease. Dermoscopy has gained increasing interest in the past few years as an aid in the clinical diagnosis of inflammatory and infectious skin manifestations. We present a case report about a single, erythematous, and asymptomatic plaque on the face with unexpected dermoscopy characteristics of CS.